Proteômica de Escherichia coli Enteropatogênica em resposta ao cinamaldeído - Gonçalves, Michelle Carlota (2021)
This study comparatively analyzed the adaptive response of the pathogenic Enteropathogenic Escherichia coli (EPEC) against cinnamaldehyde, the major component of cinnamon essential oil (Cinnamomum cassia) as an alternative to conventionally used antimicrobials. It aimed to identify which proteins, as well as adaptive mechanisms, are involved in the EPEC response to stress when subjected to a sublethal dose of the antimicrobial, favoring the adaptation of the bacteria to doses previously considered lethal. After analysis in nanoUPLC-MSE, 196 proteins were identified, distributed among the experimental groups, and of these, 107 were differentially expressed, among which 13 were overexpressed (p>0.95) and 94 underexpressed (p<0.05) in adapted cells. Of the up-regulated proteins, most are cytoplasmic and make up proteinase related to cellular metabolic processes, such as peptide-glycan anchoring lipoprotein (lpp), chaperone involved in the stress response (ClpB; groL; ahpC), proteins involved in the catalysis of enzymatic reactions accelerating metabolic reactions (pgi; pflB; grcA; deoD; gapA; tdcE), carbohydrate metabolism, amino acids (Cada), protein involved in the regulation of homeostasis (trxA) and a protein that has not yet been characterized (yfcZ). Meanwhile, translation-related proteinase, lipid biosynthesis, chromosomal condensation, acetyl-CoA biosynthetic processes, proton transport coupled to ATP synthesis, nucleic acid binding, protein and carbohydrate biosynthesis, and cell division were down-regulated, meaning that stressful agents affect cellular processes, contributing to adaptation. The results obtained in this study showed that EPEC presented significant metabolic alterations when in the presence of the antimicrobial cinnamaldehyde.